The Nazi ministerial elite: 1933-1945 - Fonseca, A. M. (2009)
Using data collected as part of the University of Lisbon's Institute of Social Science's project, Elites, single party and political decision-making in the era of fascisms: Portugal, Spain, Italy and Germany, this article seeks to describe the socio-political profile of the Third Reich's ministerial elite from 1933 to 1945, and to understand the recruitment variables that led to the appointment of these men to Hitler's government, trying to provide a political description of the Nazi ministerial elite. Above all, the case of the Third Reich demonstrates the extreme diminution of the power of government, which was achieved by strengthening the Nazi Party's parallel apparatus. In this way, the Nazi Party was transformed into practically the only recruitment source for the ministerial elite, taking control of the government while simultaneously diminishing the relevence of that elite.